"A Father and Mother More Worthy of Heaven Than of Earth": The Promotion of the Cults of Louis and Zélie Martin by the Carmel of Lisieux, 1897–19591. (7th December 2018) - Deboick, Sophia L.
Abstract : This article examines the promotion of the cults of the parents of Saint Thérèse of Lisieux by their daughters, nuns of the Carmel of Lisieux, from the time of Thérèse's death in 1897 until the late 1950s. Louis and Zélie Martin were made saints in the first joint canonisation of spouses in the history of the church in 2015 — this article traces the laying of the foundations for their official recognition well over half a century before. It examines in particular the work of Céline Martin (1869–1959), the chief promoter of Saint Thérèse's own cult and author of her popular image, in developing a public face for the Martin parents, situating this history within the interest of celebrity studies in the industrial production of celebrity. It goes on to analyse the modes in which the Martins were represented in both key images and texts — principally Céline's portraits of them and the biographies she wrote in the 1950s. It is shown that she ultimately wrote them into two devotional themes — that of sacrificial victimhood and abandonment to God's will — and in doing so cast them as precursors to Thérèse's own spiritual insights.